Window Shopping Assisted by Geoenzo to Increase Students’ Conceptual Understanding in Mathematics to Learning Interest - Fredi Ganda Putra; Dyan Revianto; Rizki Wahyu Yunian Putra; Santi Widyawati (Jurnal Inovasi Matematika, 2021)
The purposes of this research were determining (1) the effect of the Windows Shopping learning model assisted by Geoenzo on mathematical concepts understanding ability, 2) the influence of learning interest on mathematical concepts understanding ability, and 3) the interaction between Window Shopping learning model assisted by Geoenzo and learning interest towards mathematical concepts understanding ability. The sample in this study was selected using a randomized class technique, so that classes VIIA (23 students) and VIIB (24 students) in private Madrasah Tsanawiyah in the Kedondong city at 2020/2021 as a samples. This research was quasi-experimental design. The data collecting techniques used were tests, documentation, and questionnaires, which were then tested using the analysis of variance (ANOVA) test. The results showed that (1) there was an influence between the Window Shopping model assisted by Geoenzo on mathematical concepts understanding ability, (2) students’ category of learning interest (high, medium, and low) did not affect the mathematical concepts understanding ability, and (3) there was no interaction between the Window Shopping learning model assisted by geoenzo and learning interest towards students' mathematical concepts understanding ability.